Climatic conditions and farm practices affected the prevalence of Aspergillus section Flavi on different types of dairy goat's feed - Azman, Nur Izzati; Wan Mustapha, Wan Norazihan; Goh, Yong Meng; Abu Hassim, Hasliza; Selamat, Jinap; Samsudin, Nik Iskandar Putra (Elsevier, 2021)
The present work aimed to determine the prevalence of aflatoxigenic Aspergillus section Flavi on different types of dairy goat's feed samples obtained from four dairy goat's farms around the central region of Peninsular Malaysia, and to examine the effects of climatic conditions (temperature, relative humidity) of the dairy goat's farms, and their feeding and storage practices on the fungal prevalence of different types of dairy goat's feed. A total of 60 goat's feed samples were obtained, and their proximate composition and water activity were determined, following which they were cultivated on DRBC and AFPA for total fungal load and Aspergillus section Flavi load determination, respectively. Fungal isolates were identified morphologically, and toxigenicity potentials of Aspergillus section Flavi isolates were determined using CCA. The temperature and relative humidity data of all farms were obtained from the Malaysian Meteorological Department. The total fungal loads (on DRBC) of the goat's feed samples were log 0.767 to 7.071 CFU/g which included the common feed contaminants such as Aspergillus, Fusarium, and Penicillium. The Aspergillus section Flavi loads (on AFPA) were log 0.667 to 3.206 CFU/g. Farm A yielded the highest number of Aspergillus section Flavi isolates as well as the highest number of aflatoxigenic isolates. It was found that climatic conditions and different practices between farms positively influenced the fungal prevalence on goat's feed samples based on the Pearson correlation analysis. The prevalence of mycotoxigenic isolates on goat's feed warrants for urgent intervention to ensure that goats are being fed with nutritionally adequate and safe feed. The presence of aflatoxigenic Aspergillus section Flavi isolates indicates the risk of aflatoxin B1 contamination on the goat's feed, aflatoxicosis development in the goats, and aflatoxin M1 bio-transformation in the goat's milk. This is a potential threat to the flourishing goat's milk industry in Malaysia.